Telbivudine versus lamivudine in patients with chronic hepatitis B - Ching Lung Lai (2018)
BACKGROUND: Reducing hepatitis B virus (HBV) replication to minimal levels is emerging as a key therapeutic goal for chronic hepatitis B. METHODS: In this double-blind, phase 3 trial, 1370 patients with chronic hepatitis B were randomly assigned to receive 600 mg of telbivudine or 100 mg of lamivudine once daily. The primary efficacy end point was noninferiority of telbivudine to lamivudine for therapeutic response (i.e., a reduction in serum HBV DNA levels to fewer than 5 log10copies per milliliter, along with loss of hepatitis B e antigen [HBeAg] or normalization of alanine aminotransferase levels). Secondary efficacy measures included histologic response, changes in serum HBV DNA levels, and HBeAg responses. RESULTS: At week 52, a significantly higher proportion of HBeAg-positive patients receiving telbivudine than of those receiving lamivudine had a therapeutic response (75.3% vs. 67.0%, P = 0.005) or a histologic response (64.7% vs. 56.3%, P = 0.01); telbivudine also was not inferior to lamivudine for these end points in HBeAg-negative patients. In HBeAg-positive and HBeAg-negative patients, telbivudine was superior to lamivudine with respect to the mean reduction in the number of copies of HBV DNA from baseline, the proportion of patients with a reduction in HBV DNA to levels undetectable by polymerase-chain-reaction assay, and development of resistance to the drug. Elevated creatine kinase levels were more common in patients who received telbivudine, whereas elevated alanine aminotransferase and aspartate aminotransferase levels were more common in those who received lamivudine. CONCLUSIONS: Among patients with HBeAg-positive chronic hepatitis B, the rates of therapeutic and histologic response at 1 year were significantly higher in patients treated with telbivudine than in patients treated with lamivudine. In both the HBeAg-negative and the HBeAg-positive groups, telbivudine demonstrated greater HBV DNA suppression with less resistance than did lamivudine. (ClinicalTrials.gov number, NCT00057265.) Copyright © 2007 Massachusetts Medical Society.